Focal Treatment of Prostate Cancer with Vascular-Targeted Photodynamic Therapy - Scott E. Eggener; Jonathan A. Coleman (The Scientific World Journal)
Epidemiologic and pathologic features of prostate cancer have given rise to an interest in focal treatment for carefully selected patients. Prostate cancer remains highly prevalent, particularly in the U.S. and Europe. As screening programs have become more aggressive and widespread, a substantial proportion of men diagnosed with localized prostate cancer have disease characteristics associated with a low risk of progression. Treatments such as radical prostatectomy and radiation therapy can lead to durable recurrence-free survival in most patients, but carry variable risks of bowel, urinary, and sexual side effects. Few men and few urologists are comfortable leaving a potentially curable prostate cancer untreated. Focal therapy offers an attractive alternative for the patient faced with a choice between aggressive local intervention (radiation or surgery) and watchful waiting. Contemporary diagnostic biopsy strategies and imaging tools, and the development of predictive statistical models (nomograms), have led to improvements in tumor characterization and risk stratification, making focal therapy a viable treatment option for specific men. This article reviews the rationale and indications for focal therapy and highlights vascular-targeted photodynamic therapy (PDT) as one of many promising focal therapy techniques.